LOYALITAS KERJA GURU DALAM PERSPEKTIF STUDI LITERATUR : ANTARA MOTIVASI, KEPUASAN KERJA, LINGKUNGAN KERJA DAN KOMPENSASI - Fitria Elvi (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to analyze teacher job loyalty through a literature review approach by examining the influencing factors, namely motivation, job satisfaction, work environment, and compensation. Teacher job loyalty is a crucial aspect in maintaining the quality of education, as loyal teachers tend to demonstrate high levels of dedication, discipline, and commitment in carrying out their professional duties. The literature review indicates that motivation plays a central role in encouraging teachers to perform optimally, while job satisfaction is closely related to the sense of comfort, recognition, and appreciation that teachers experience in their work. The work environment, both physical and non-physical, also contributes to determining loyalty, as a supportive atmosphere can strengthen teachers’ emotional and professional attachment to the school. Furthermore, fair and appropriate compensation significantly supports loyalty, as it represents a tangible form of recognition for teachers’ contributions. The findings of this literature synthesis suggest that these four factors are interrelated and collectively shape teachers’ job loyalty. This study highlights the importance of educational management in paying close attention to teachers’ welfare, motivation, and working conditions to cultivate a loyal, competent, and sustainable teaching workforce.